(untitled) (Res Medica, 2013)
TABLE OF CONTENTS PERFUSION: Professor W.A. Mackey ABDOMINAL CRISES 1: I.S.R. Sinclair, F.R.C.S. FIBRINOLYSIS AND OCCLUSIVE VASCULAR DISEASE: J.D. Cash, B.Sc., M.B., CH.B. RES MEDICA THE UNBORN CHILD: Professor C.S. Russell THE USE OF CONTROLS IN THE ASSESSMENT OF CLINICAL EVIDENCE: C.V. Ruckley, M.B., CH.B. "THE SLIMY MUD OF WORDS":H.C. Drysdale, M.B., CH.B. THE HARVEIAN ORATION, 1961: Dr. J.K. Slater, O.B.E., M.D. MELANCHOLIA: E.B. Ritson, M.B., CH.B.